Imbalance of Rights and Obligations of Husband and Wife in the Family - Apriana, Dian; Silvia, Nanda; Emmanuel, Uwem Imoh (Faculty of Sharia, IAIN Metro, 2022)
Marriage is a worship and complement of religion, marriage is also one of the scopes of discussions on Family Law. Marriage is the sunnah of the Prophet SAW. Marriage is a human right given by Allah SWT. To create a family that is sakinah mawadah, warohmah besides that the purpose of marriage is to continue the offspring, and to carry out its biological integrity. In the Department of Family Law, marriage is discussed in detail in order to create a marriage according to the Shari'a of Allah SWT. This article is entitled The Need for Rights and Obligations of Husband and Wife in the Family. This paper aims to find out what are the rights and obligations of a husband and wife in a household. In writing it uses research methods by collecting data from journals related to this discussion.